Perceived Socio-cultural Barriers to Children ’ s Acquisition of Kiswahili Pre-Reading Skills in Rural Pre-primary Schools in Tanzania - Edward, Geraldina Edward; Shukia, Richard Shukia (Papers in Education and Development, 2023)
This paper explores socio-cultural barriers to children ' s acquisition of Kiswahili pre-reading skills in rural public €“pre-primary schools in Tanzania. Purposive sampling was used to obtain 48 pre-primary school teachers, head teachers and parents. Data were collected through semistructured interview and focus group discussion methods. Thematic analysis was utilised in data analysis using NVivo-12 software for qualitative and non-structured data. The findings revealed that mother-tongue interference, limited parent-teacher collaboration and community beliefs about children ' s education were the perceived socio-cultural barriers to children ' s acquisition of Kiswahili pre-reading skills. The paper concludes that children ' s acquisition of Kiswahili pre-reading skills was hampered by the presence of various socio-cultural barriers. The paper recommends that pre-primary school learning environments in rural areas should be improved for children ' s successful acquisition of pre-reading skills. Keywords: early childhood education, Kiswahili language, marginalised schools, reading acquisition, socio-cultural barriers